Bertrand Russell's best - Russell, Bertrand (Routledge, 2009)
Bertrand Russell was regarded as one of the twentieth century's greatest minds. Well known for his profound knowledge and controversial approach to a myriad of different issues and subjects, his prolific works also exhibited great intellectual wit and humour. Bertrand Russell's Best is a collection of Russell's wittiest and most pungent writings. First published in 1958, this delightfully funny and entertaining book is a striking testament to the remarkable life, work and wit of Bertrand Russell.